Structural Analysis in Shoufengsi Area of Tananao Complex, Eastern Taiwan - Gong-Ruei Ho and Wei Lo (Terrestrial, Atmospheric and Oceanic Sciences, 2015)

(untitled)
The subduction and collision boundaries of the Eurasia and Philippine Sea Plates in the Taiwan mountain belt expose a NE-trending coherent crustal section in the Tananao Complex. This study investigates the structures in three dimensions in the Shoufengsi area, which is located in the middle section of the Tananao Complex to understand the Taiwan orogeny mountain building processes. Detailed geological mapping and structural analyses shows the eastward shortening associated with metamorphism indicative of three deformation events. Three sets of axial plane foliation S1, S2, and S3 can be recognized by Type-1 and Type-3 fold interference patterns. Different structural characteristics can be further revealed in five domains based on domain analysis. Each domain shows the superposed process characteristics. Synthetic structural mapping and microstructure examination analyses on the Shoufengsi area show that NE-trending isoclinal folds and axial D1 and D2 plane foliation events represent shortening deformation and NW-trending crenulation cleavage. Normal D3 event faults display the gravity collapse deformation. These observations are consistent with shortening to extension stage predictions during Eurasia and Philippine Sea Plate collisions.